Method for forming resist pattern

JP7643204B2Active Publication Date: 2025-03-11ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021104458
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-23
Publication Date
2025-03-11
Estimated Expiration
2041-06-23

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、レジストパターントップの減りが少なく、かつ、コントラストの高いレジストパターンを形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643204000001
    Figure 0007643204000001
  • Figure 0007643204000002
    Figure 0007643204000002
  • Figure 0007643204000003
    Figure 0007643204000003
Patent Text Reader

Abstract

To provide a resist pattern forming method capable of forming a resist pattern with little loss of a resist pattern top and high contrast.SOLUTION: The resist pattern forming method comprises: forming a resist film using a positive resist composition which contains a main chain scission-type copolymer A containing a fluorine substituent, a main chain scission-type copolymer B containing a fluorine substituent, and a solvent and in which the difference between the surface free energy of the copolymer A and the surface free energy of the copolymer B is 4 mJ / m2 or more; exposing the resist film; and developing the exposed resist film using a developer containing at least a solvent having a solubility parameter of 8 (cal / cm3)1 / 2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method of forming a resist pattern, and in particular to a method of forming a resist pattern using a positive resist composition. [Background technology]

[0002] Conventionally, in the field of semiconductor manufacturing and the like, polymers whose main chains are cleaved and whose solubility in a developer is increased by irradiation with ionizing radiation such as electron beams or short-wavelength light such as ultraviolet light (hereinafter, ionizing radiation and short-wavelength light may be collectively referred to as "ionizing radiation, etc.") have been used as main-chain scission type positive resists.

[0003] For example, Patent Document 1 discloses a positive resist composition that contains a positive resist made of a copolymer containing α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and α-methylstyrene units, as a main chain scission type positive resist that has excellent heat resistance and sensitivity to ionizing radiation and the like. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-154754 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the resist patterns formed using the above-mentioned conventional positive resist compositions have room for improvement in terms of reducing top loss of the resist pattern and increasing the contrast of the resist pattern.

[0006] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a method for forming a resist pattern which reduces loss of the top of the resist pattern and is capable of forming a resist pattern with high contrast. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to achieve the above object, and have newly discovered that a resist pattern with high contrast and reduced loss of the top of the resist pattern can be formed by forming a resist film using a positive resist composition containing two types of specified copolymers as a positive resist and developing the exposed resist film using a specified developer, thereby completing the present invention.

[0008] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the method for forming a resist pattern of the present invention comprises a main chain scission type copolymer A containing a fluorine substituent, a main chain scission type copolymer B containing a fluorine substituent, and a solvent, and the difference in surface free energy between the copolymer A and the copolymer B is 4 mJ / m 2 a resist film forming step of forming a resist film using the positive resist composition having the above composition; an exposure step of exposing the resist film to light; and a resist film having a solubility parameter of 8 (cal / cm 3 ) 1 / 2 and a developing step of developing the resist using a developer containing at least a solvent having a surface free energy difference of 4 mJ / m or less. 2 A resist film is formed using a positive resist composition containing the above copolymer A and copolymer B, and the resist film is exposed to light. The exposed resist film is then treated with a solvent having a solubility parameter of 8 (cal / cm 3 ) 1 / 2 When development is performed using a developer containing at least the following solvent, loss of the top of the resist pattern is small and a resist pattern with high contrast can be formed. In the present invention, the copolymer being "main chain scission type" means that the copolymer has the property of having a main chain that is scissioned when the copolymer is irradiated with ionizing radiation such as an electron beam or extreme ultraviolet (EUV) radiation. In the present invention, the "surface free energy" and the "solubility parameter" (hereinafter also referred to as "SP value") can be calculated using the method described in the Examples of this specification.

[0009] In the method for forming a resist pattern of the present invention, the copolymer A is represented by the following formula (I): [ka] [In the formula (I), L is a divalent linking group having a fluorine atom, and Ar is an aromatic ring group which may have a substituent.], The following formula (II): [ka] [In formula (II), R 1 is an alkyl group, R 2 is a hydrogen atom, an alkyl group, a halogen atom, a halogenated alkyl group, a hydroxyl group, a carboxyl group, or a halogenated carboxyl group, and R 3 is a hydrogen atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and p and q are integers of 0 to 5, and p+q=5. By using copolymer A having monomer unit (I) and monomer unit (II), the contrast of the resist pattern can be further increased. In the present invention, the phrase "optionally having a substituent" means "unsubstituted or having a substituent".

[0010] In the method for forming a resist pattern of the present invention, the copolymer B is represented by the following formula (III): [ka] [In formula (III), R 1is an organic group having 5 to 7 fluorine atoms; The following formula (IV): [ka] [In formula (IV), R 1 is an alkyl group, R 2 is a hydrogen atom, a fluorine atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and R 3 is a hydrogen atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and p and q are integers of 0 to 5, and p+q=5. By using copolymer B having monomer unit (III) and monomer unit (IV), the contrast of the resist pattern can be further increased.

[0011] Furthermore, in the method for forming a resist pattern of the present invention, the developing step is carried out using a compound having a solubility parameter of 8 (cal / cm 3 ) 1 / 2 It is preferable that the development step includes a process (1) of developing using a developer (1) having a solubility parameter of 8 (cal / cm or less) or less and a process (2) of developing using a developer (2) different from the developer (1), and that the processes (1) and (2) are carried out in this order. 3 ) 1 / 2 If development is carried out using the following solvent as developer (1), and then, as treatment (2), development is carried out using a developer (2) different from developer (1), it is possible to efficiently form a resist pattern with less loss of the top of the resist pattern and with higher contrast.

[0012] In the method for forming a resist pattern of the present invention, the developer (1) is preferably a hydrocarbon-based solvent. By using a hydrocarbon-based solvent as the developer (1), the contrast of the resist pattern can be further increased.

[0013] In the method for forming a resist pattern of the present invention, the developer (2) is preferably an alcohol-based solvent. By using an alcohol-based solvent as the developer (2), the contrast of the resist pattern can be further increased. Effect of the Invention

[0014] According to the present invention, a resist pattern with high contrast and with little loss of the top of the resist pattern can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described in detail. The method for forming a resist pattern of the present invention is a method for forming a resist pattern using ionizing radiation such as an electron beam and EUV, etc. The method for forming a resist pattern of the present invention is not particularly limited and can be used, for example, when forming a resist pattern in a manufacturing process of a semiconductor, a photomask, a mold, etc.

[0016] (Method of forming a resist pattern) The method for forming a resist pattern of the present invention includes a step of forming a resist film using a specific positive resist composition described in detail below (resist film forming step), a step of exposing the resist film to light (exposure step), and a step of developing the exposed resist film using a specific developer described in detail below (development step).

[0017] The resist pattern forming method of the present invention may further include a step other than the resist film forming step, the exposure step, and the development step described above. Specifically, the resist pattern forming method of the present invention may include a step (underlayer film forming step) of forming an underlayer film on the substrate on which the resist film is to be formed, before the resist film forming step. The resist pattern forming method of the present invention may also include a step (post-exposure bake step) of heating the exposed resist film between the exposure step and the development step. The resist pattern forming method of the present invention may also include a step (rinsing step) of removing the developer after the development step. After the resist pattern is formed by the resist pattern forming method of the present invention, the resist pattern forming method may also include a step (etching step) of etching the underlayer film and / or the substrate.

[0018] Furthermore, in the method of forming a resist pattern of the present invention, a resist film is formed using a positive resist composition containing a specified copolymer, and in the developing step, the resist film is developed using a specified developer, thereby making it possible to form a resist pattern with high contrast and with minimal reduction in the top of the resist pattern. Each step in the method for forming a resist pattern of the present invention will be described in order below.

[0019] <Lower film formation process> In the underlayer film forming step, which may be optionally performed before the resist film forming step, an underlayer film is formed on a substrate. By providing the underlayer film on the substrate, the surface of the substrate is made hydrophobic. This increases the affinity between the substrate and the resist film, and can increase the adhesion between the substrate and the resist film. The underlayer film may be an inorganic underlayer film or an organic underlayer film.

[0020] -substrate- Here, the substrate is not particularly limited, and examples of the substrate that can be used include a substrate having an insulating layer and a copper foil provided on the insulating layer, which is used in the manufacture of printed circuit boards, and a mask blank having a light-shielding layer formed on a substrate.

[0021] The substrate material may be, for example, metal (silicon, copper, chromium, iron, aluminum, etc.), glass, titanium oxide, silicon dioxide (SiO 2 Examples of the substrate include inorganic materials such as silica and mica; nitrides such as SiN; oxynitrides such as SiON; and organic materials such as acrylic, polystyrene, cellulose, cellulose acetate, and phenol resin. Among these, metals are preferred as the substrate material. By using, for example, a silicon substrate, a silicon dioxide substrate, or a copper substrate, preferably a silicon substrate or a silicon dioxide substrate, as the substrate, a cylindrical structure can be formed.

[0022] The size and shape of the substrate are not particularly limited. The surface of the substrate may be smooth, may have a curved surface or an uneven surface, or may be a thin plate-shaped substrate.

[0023] Furthermore, the surface of the substrate may be subjected to a surface treatment as necessary. For example, in the case of a substrate having a hydroxyl group on the surface layer of the substrate, the surface of the substrate can be treated with a silane coupling agent capable of reacting with the hydroxyl group. This changes the surface layer of the substrate from hydrophilic to hydrophobic, thereby improving the adhesion between the substrate and the underlayer film or between the substrate and the resist layer. In this case, the silane coupling agent is not particularly limited, but hexamethyldisilazane is preferred.

[0024] The inorganic underlayer film provided on the substrate can be formed, for example, by applying an inorganic material onto the substrate and baking it, etc. Examples of the inorganic material include silicon-based materials.

[0025] The organic underlayer film provided on the substrate can be formed, for example, by applying an organic material onto the substrate to form a coating film and drying it. The organic material is not limited to those having sensitivity to light or electron beams, and can be, for example, a resist material or a resin material commonly used in the semiconductor field and liquid crystal field. Among them, the organic material is preferably a material capable of forming an organic underlayer film capable of etching, particularly dry etching. With such an organic material, the pattern formed by processing the resist film can be used to etch the organic underlayer film, thereby transferring the pattern to the underlayer film to form a pattern of the underlayer film. Among them, the organic material is preferably a material capable of forming an organic underlayer film capable of etching, such as oxygen plasma etching. Examples of organic materials used for forming the organic underlayer film include AL412 from Brewer Science.

[0026] The organic material can be applied by a conventional method using spin coating or a spinner. The method for drying the coating film may be any method capable of volatilizing the solvent contained in the organic material, such as a baking method. The baking conditions are not particularly limited, but the baking temperature is preferably 80°C or more and 300°C or less, and more preferably 200°C or more and 300°C or less. The baking time is preferably 30 seconds or more, more preferably 60 seconds or more, preferably 500 seconds or less, more preferably 400 seconds or less, even more preferably 300 seconds or less, and particularly preferably 180 seconds or less. The thickness of the underlayer film after drying the coating film is not particularly limited, but is preferably 10 nm or more and 100 nm or less.

[0027] <Resist film formation process> In the resist film forming step, a specific positive resist composition used in the resist pattern forming method of the present invention is applied onto a substrate to be processed using the resist pattern (on the underlayer film if an underlayer film is formed), and the applied positive resist composition is dried to form a resist film. The substrate used in the resist film forming step is not particularly limited, and for example, the substrate explained in <Underlayer film forming step> can be used.

[0028] [Positive resist composition] The positive resist composition used in the resist film forming step contains copolymer A, copolymer B, and a solvent, and optionally further contains known additives that can be blended into positive resist compositions. It is preferable that the positive resist composition does not substantially contain components with a weight average molecular weight (Mw) of less than 1000. Specifically, the content of components with a weight average molecular weight (Mw) of less than 1000 in the positive resist composition is preferably less than 0.05 mass%, more preferably less than 0.01 mass%, and even more preferably less than 0.001 mass%.

[0029] [Copolymer A] Copolymer A contained in the positive resist composition is a main chain cleavage type copolymer containing a fluorine substituent. The fluorine substituent is not particularly limited as long as it is a substituent having a fluorine atom.

[0030] [Surface free energy of copolymer A] Here, the surface free energy of copolymer A is 28 mJ / m 2 More preferably, 29 mJ / m 2 More preferably, it is 30 mJ / m or more. 2 More preferably, it is 35 mJ / m or more. 2 Preferably, it is 34 mJ / m or less. 2 More preferably, it is 33 mJ / m or less. 2 It is even more preferable that:

[0031] From the viewpoint of further enhancing the contrast of the resist pattern, copolymer A is a copolymer represented by the following formula (I): [ka] [In the formula (I), L is a divalent linking group having a fluorine atom, and Ar is an aromatic ring group which may have a substituent.], The following formula (II): [ka] [In formula (II), R 1 is an alkyl group, R 2 is a hydrogen atom, an alkyl group, a halogen atom, a halogenated alkyl group, a hydroxyl group, a carboxyl group, or a halogenated carboxyl group, and R 3 is a hydrogen atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and p and q are integers of 0 or more and 5 or less, and p+q=5.

[0032] Copolymer A may contain any monomer unit other than monomer unit (I) and monomer unit (II). However, the total proportion of monomer unit (I) and monomer unit (II) in all monomer units constituting copolymer A is preferably 90 mol % or more, and more preferably 100 mol % (i.e., copolymer A contains only monomer unit (I) and monomer unit (II)).

[0033] Since copolymer A contains monomer units (I) and (II), when it is irradiated with an electron beam or the like, the main chain is cut and the molecular weight is reduced.

[0034] -Monomer unit (I)- Here, the monomer unit (I) is represented by the following formula (a): [ka] [In the formula (a), L and Ar are the same as those in the formula (I)].

[0035] Examples of the divalent linking group having a fluorine atom which can constitute L in formula (I) and formula (a) include a divalent chain alkyl group having 1 to 5 carbon atoms and having a fluorine atom.

[0036] Moreover, Ar in the formula (I) and the formula (a) includes an aromatic hydrocarbon ring group which may have a substituent and an aromatic heterocyclic group which may have a substituent.

[0037] The aromatic hydrocarbon ring group is not particularly limited, and examples thereof include a benzene ring group, a biphenyl ring group, a naphthalene ring group, an azulene ring group, an anthracene ring group, a phenanthrene ring group, a pyrene ring group, a chrysene ring group, a naphthacene ring group, a triphenylene ring group, an o-terphenyl ring group, an m-terphenyl ring group, a p-terphenyl ring group, an acenaphthene ring group, a coronene ring group, a fluorene ring group, a fluoranthrene ring group, a pentacene ring group, a perylene ring group, a pentaphene ring group, a picene ring group, and a pyranthrene ring group.

[0038] Furthermore, examples of the aromatic heterocyclic group include, but are not limited to, a furan ring group, a thiophene ring group, a pyridine ring group, a pyridazine ring group, a pyrimidine ring group, a pyrazine ring group, a triazine ring group, an oxadiazole ring group, a triazole ring group, an imidazole ring group, a pyrazole ring group, a thiazole ring group, an indole ring group, a benzimidazole ring group, a benzothiazole ring group, a benzoxazole ring group, a quinoxaline ring group, a quinazoline ring group, a phthalazine ring group, a benzofuran ring group, a dibenzofuran ring group, a benzothiophene ring group, a dibenzothiophene ring group, and a carbazole ring group.

[0039] Furthermore, the substituent that Ar may have is not particularly limited, and examples thereof include an alkyl group, a fluorine atom, and a fluoroalkyl group. Examples of the alkyl group as the substituent that Ar may have include a chain alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an n-butyl group, and an isobutyl group. Examples of the fluoroalkyl group as the substituent that Ar may have include a fluoroalkyl group having 1 to 5 carbon atoms, such as a trifluoromethyl group, a trifluoroethyl group, and a pentafluoropropyl group.

[0040] Among these, from the viewpoint of sufficiently improving the sensitivity to an electron beam or the like, Ar in formula (I) and formula (a) is preferably an aromatic hydrocarbon ring group which may have a substituent, more preferably an unsubstituted aromatic hydrocarbon ring group, and even more preferably a benzene ring group (phenyl group).

[0041] From the viewpoint of sufficiently improving the sensitivity to electron beams and the like, the monomer (a) represented by the above formula (a) capable of forming the monomer unit (I) represented by the above formula (I) is preferably α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl (ACAFPh) and α-chloroacrylate-1-(4-methoxyphenyl)-1-trifluoromethyl-2,2,2-trifluoroethyl (ACAFPhOMe), more preferably α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl. That is, copolymer A preferably has at least one of α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and α-chloroacrylate-1-(4-methoxyphenyl)-1-trifluoromethyl-2,2,2-trifluoroethyl units, and more preferably has α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units.

[0042] The proportion of the monomer units (I) in all the monomer units constituting the copolymer A is not particularly limited, and can be, for example, 30 mol % or more and 70 mol % or less.

[0043] The monomer unit (II) is represented by the following formula (b): [ka] [In formula (b), R 1 ~R 3 and p and q are the same as in formula (II).

[0044] Here, R in formula (II) and formula (b) 1 ,R 2 The alkyl group that can constitute R is not particularly limited, and examples thereof include unsubstituted alkyl groups having 1 to 5 carbon atoms. 1 , R 2 The alkyl group which can constitute the above group is preferably a methyl group or an ethyl group.

[0045] In addition, R in formula (II) and formula (b) 2 The halogen atom which can constitute the ring structure is not particularly limited, and examples thereof include a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc. Among these, the halogen atom is preferably a fluorine atom.

[0046] Furthermore, R in formula (II) and formula (b) 2 The halogenated alkyl group that can constitute the above is not particularly limited, and examples thereof include fluoroalkyl groups having 1 to 5 carbon atoms. Among them, the halogenated alkyl group is preferably a perfluoroalkyl group having 1 to 5 carbon atoms, and more preferably a trifluoromethyl group.

[0047] Furthermore, R in formula (II) and formula (b) 2Examples of halogenated carboxyl groups that can constitute the above formula include, but are not limited to, a chlorocarboxyl group (-C(=O)-Cl), a fluorinated carboxyl group (-C(=O)-F), and a brominated carboxyl group (-C(=O)-Br).

[0048] In addition, R in formula (II) and formula (b) 3 The unsubstituted alkyl group that can constitute R is not particularly limited, and examples thereof include unsubstituted alkyl groups having 1 to 5 carbon atoms. 3 The unsubstituted alkyl group which may constitute the above formula is preferably a methyl group or an ethyl group.

[0049] In addition, R in formula (II) and formula (b) 3 The fluorine-substituted alkyl group that can constitute the above formula is not particularly limited, and examples thereof include groups having a structure in which some or all of the hydrogen atoms of an alkyl group are substituted with fluorine atoms.

[0050] From the viewpoint of easiness of preparation of the copolymer A and improvement of scission property of the main chain when irradiated with an electron beam or the like, R 1 is preferably an alkyl group having 1 to 5 carbon atoms, and more preferably a methyl group.

[0051] From the viewpoints of easiness in preparation of Copolymer A and improvement in severability of the main chain when irradiated with an electron beam or the like, p in formula (b) of formula (II) is preferably 0 or 1.

[0052] Furthermore, when p in formula (II) and formula (b) is any one of 1 to 5, R 2 is preferably an alkyl group having 1 to 5 carbon atoms, and more preferably a methyl group.

[0053] The monomer (b) represented by the above formula (b) capable of forming the monomer unit (II) represented by the above formula (II) is not particularly limited, and examples thereof include α-methylstyrene (AMS) and its derivatives such as the following monomers (b-1) to (b-12). [ka]

[0054] From the viewpoints of ease of preparation of copolymer A and improving the severability of the main chain when irradiated with an electron beam or the like, the monomer (b) represented by the above formula (b) capable of forming the monomer unit (II) is preferably α-methylstyrene. That is, copolymer A preferably has an α-methylstyrene unit.

[0055] The proportion of the monomer units (II) in all the monomer units constituting the copolymer A is not particularly limited, and can be, for example, 30 mol % or more and 70 mol % or less.

[0056] -Properties of copolymer A- =Weight average molecular weight (Mw)= The weight average molecular weight (Mw) of copolymer A is preferably 100,000 or more, more preferably 125,000 or more, even more preferably 150,000 or more, and preferably 600,000 or less, more preferably 500,000 or less. If the weight average molecular weight (Mw) of copolymer A is the above lower limit or more, the loss of the resist pattern top can be further reduced, and a resist pattern with further improved contrast can be formed. In addition, if the weight average molecular weight (Mw) of copolymer A is the above upper limit or less, the positive resist composition can be easily adjusted.

[0057] =Number average molecular weight (Mn)= The number average molecular weight (Mn) of copolymer A is preferably 100,000 or more, more preferably 110,000 or more, and preferably 300,000 or less, and more preferably 200,000 or less. If the number average molecular weight of copolymer A is equal to or greater than the lower limit, the loss of the resist pattern top can be further reduced, and a resist pattern with further improved contrast can be formed. If the number average molecular weight of copolymer A is equal to or less than the upper limit, the preparation of a positive resist composition is even easier.

[0058] =Molecular weight distribution (Mw / Mn)= The molecular weight distribution (Mw / Mn) of copolymer A is preferably 1.20 or more, more preferably 1.25 or more, and even more preferably 1.30 or more, and is preferably 2.00 or less, more preferably 1.80 or less, and even more preferably 1.60 or less. In the present invention, the "number average molecular weight" can be measured using gel permeation chromatography in terms of standard polystyrene, and the "molecular weight distribution" can be determined by calculating the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight).

[0059] -Method for preparing copolymer A- The copolymer A having the above-mentioned monomer unit (I) and monomer unit (II) can be prepared, for example, by polymerizing a monomer composition containing the monomer (a) and the monomer (b), recovering the obtained copolymer, and optionally purifying it. The composition, molecular weight distribution, number average molecular weight and weight average molecular weight of copolymer A can be adjusted by changing the polymerization conditions and purification conditions. Specifically, for example, the number average molecular weight and weight average molecular weight can be increased by lowering the polymerization temperature. Also, the number average molecular weight and weight average molecular weight can be increased by shortening the polymerization time. Furthermore, the molecular weight distribution can be narrowed by purification.

[0060] Polymerization of Monomer Composition Here, the monomer composition used for preparing the copolymer A can be a mixture of monomer components including monomer (a) and monomer (b), an optional solvent, an optional polymerization initiator, and optional additives. The polymerization of the monomer composition can be carried out using a known method. Among them, it is preferable to use cyclopentanone, water, etc. as the solvent.

[0061] Furthermore, the polymer obtained by polymerizing the monomer composition can be recovered by adding a good solvent such as tetrahydrofuran to a solution containing the polymer, and then dropping the solution to which the good solvent has been added into a poor solvent such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, or hexane to solidify the polymer, without any particular limitation.

[0062] =Purification of Polymer= The purification method used for purifying the obtained polymer is not particularly limited, and examples thereof include known purification methods such as reprecipitation and column chromatography. Among them, the reprecipitation method is preferably used as the purification method. The purification of the polymer may be repeated several times.

[0063] The purification of the polymer by the reprecipitation method is preferably carried out, for example, by dissolving the obtained polymer in a good solvent such as tetrahydrofuran, and then dropping the obtained solution into a mixed solvent of a good solvent such as tetrahydrofuran and a poor solvent such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, hexane, etc., to precipitate a part of the polymer. In this way, if the solution of the polymer is dropped into a mixed solvent of a good solvent and a poor solvent to perform purification, the molecular weight distribution, number average molecular weight, and weight average molecular weight of the obtained copolymer can be easily adjusted by changing the type and mixing ratio of the good solvent and the poor solvent. Specifically, for example, the molecular weight of the copolymer precipitated in the mixed solvent can be increased by increasing the ratio of the good solvent in the mixed solvent.

[0064] In the case of purifying the polymer by the reprecipitation method, the polymer precipitated in the mixed solvent of the good solvent and the poor solvent may be used as the copolymer A, as long as it satisfies the desired properties, or the polymer not precipitated in the mixed solvent (i.e., the polymer dissolved in the mixed solvent) may be used. Here, the polymer not precipitated in the mixed solvent can be recovered from the mixed solvent by a known method such as concentration to dryness.

[0065] [Copolymer B] The copolymer B contained in the positive resist composition is a main chain cleavage type copolymer containing a fluorine substituent. The difference in surface free energy between the copolymer B and the copolymer A is 4 mJ / m 2 The fluorine substituent is not particularly limited as long as it is a substituent having a fluorine atom.

[0066] [Surface free energy of copolymer B] Here, the surface free energy of copolymer B is 18 mJ / m 2 More preferably, it is 19 mJ / m 2 More preferably, it is 20 mJ / m or more. 2 More preferably, it is 27 mJ / m or more. 2 Preferably, it is 26 mJ / m or less. 2 More preferably, it is 25 mJ / m or less. 2 It is even more preferable that:

[0067] The difference between the surface free energy of copolymer B and that of copolymer A [i.e., the value of (surface free energy of copolymer A) - (surface free energy of copolymer B)] is 4 mJ / m 2 The difference must be 5.5 mJ / m 2 More preferably, it is 6 mJ / m or more. 2 More preferably, it is 6.5 mJ / m or more. 2 More preferably, it is 12 mJ / m or more. 2 It is preferable that the concentration is less than 11 mJ / m 2More preferably, it is 10 mJ / m or less. 2 It is even more preferable that:

[0068] From the viewpoint of further enhancing the contrast of the resist pattern, copolymer B is a copolymer represented by the following formula (III): [ka] [In formula (III), R 1 is an organic group having 5 to 7 fluorine atoms.] and a monomer unit (III) represented by the following formula (IV): [ka] [In formula (IV), R 1 is an alkyl group, R 2 is a hydrogen atom, a fluorine atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and R 3 is a hydrogen atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, and p and q are integers of 0 or more and 5 or less, and p+q=5.

[0069] Copolymer B may contain any monomer unit other than monomer unit (III) and monomer unit (IV). However, the total proportion of monomer unit (III) and monomer unit (IV) in all monomer units constituting copolymer B is preferably 90 mol % or more, and more preferably 100 mol % (i.e., copolymer B contains only monomer unit (III) and monomer unit (IV)).

[0070] Since copolymer B contains monomer units (III) and (IV), the main chain is cut and the molecular weight is reduced when irradiated with an electron beam, etc. Furthermore, since at least the monomer unit (III) of copolymer B contains a fluorine atom, the surface free energy of copolymer B can be easily adjusted, and copolymer B has resistance to forward scattering and back scattering caused by an electron beam and leakage light such as EUV, thereby enabling the pattern contrast to be further increased.

[0071] Here, the monomer unit (III) is represented by the following formula (c): [ka] [In formula (c), R 1 is the same as that of the formula (III).

[0072] In the formula (III) and the formula (c), R 1 The number of carbon atoms is preferably 2 to 10, more preferably 5 or less. When the number of carbon atoms is equal to or more than the lower limit, the solubility in the developer can be sufficiently improved. When the number of carbon atoms is equal to or less than the upper limit, the clarity of the resist pattern can be sufficiently ensured.

[0073] Specifically, R in formula (III) and formula (c) 1 R is preferably a fluoroalkyl group, a fluoroalkoxyalkyl group, or a fluoroalkoxyalkenyl group, and more preferably a fluoroalkyl group. 1 When is the above-mentioned group, the scission property of the main chain of copolymer B when irradiated with an electron beam or the like can be sufficiently improved.

[0074] Examples of the fluoroalkyl group include a 2,2,3,3,3-pentafluoropropyl group (having 5 fluorine atoms and 3 carbon atoms), a 3,3,4,4,4-pentafluorobutyl group (having 5 fluorine atoms and 4 carbon atoms), a 1H-1-(trifluoromethyl)trifluoroethyl group (having 6 fluorine atoms and 3 carbon atoms), a 1H,1H,3H-hexafluorobutyl group (having 6 fluorine atoms and 4 carbon atoms), a 2,2,3,3,4,4,4-heptafluorobutyl group (having 7 fluorine atoms and 4 carbon atoms), and a 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl group (having 7 fluorine atoms and 3 carbon atoms). Among these, a 2,2,3,3,3-pentafluoropropyl group (having 5 fluorine atoms and 3 carbon atoms) or a 2,2,3,3,4,4,4-heptafluorobutyl group (having 7 fluorine atoms and 4 carbon atoms) is preferred, and a 2,2,3,3,3-pentafluoropropyl group (having 5 fluorine atoms and 3 carbon atoms) is more preferred. Examples of the fluoroalkoxyalkyl group include a fluoroethoxymethyl group and a fluoroethoxyethyl group. Furthermore, examples of the fluoroalkoxyalkenyl group include a fluoroethoxyvinyl group.

[0075] The monomer (c) represented by the above formula (c) capable of forming the monomer unit (III) represented by the above formula (III) is not particularly limited, and examples thereof include α-chloroacrylic acid fluoroalkyl esters such as 2,2,3,3,3-pentafluoropropyl α-chloroacrylate, 3,3,4,4,4-pentafluorobutyl α-chloroacrylate, 1H-1-(trifluoromethyl)trifluoroethyl α-chloroacrylate, 1H,1H,3H-hexafluorobutyl α-chloroacrylate, 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl α-chloroacrylate, and 2,2,3,3,4,4,4-heptafluorobutyl α-chloroacrylate; α-chloroacrylic acid fluoroalkoxyalkyl esters such as α-chloroacrylic acid pentafluoroethoxymethyl ester and α-chloroacrylic acid pentafluoroethoxyethyl ester; and α-chloroacrylic acid fluoroalkoxyalkenyl ester such as α-chloroacrylic acid pentafluoroethoxyvinyl ester.

[0076] From the viewpoint of further improving the severability of the main chain of copolymer B when irradiated with an electron beam or the like, it is preferable that the monomer unit (III) is a structural unit derived from an α-chloroacrylic acid fluoroalkyl ester.

[0077] The monomer unit (IV) is represented by the following general formula (d): [ka] [In formula (d), R 1 ~R 3 and p and q are the same as in formula (IV).

[0078] Here, R in formula (IV) and formula (d) 1 The alkyl group that can constitute R is not particularly limited, and examples thereof include alkyl groups having 1 to 5 carbon atoms. 1 The alkyl group which can constitute the above group is preferably a methyl group or an ethyl group.

[0079] In addition, R in formula (IV) and (d) 2 ,R 3 The unsubstituted alkyl group that can constitute R is not particularly limited, and examples thereof include unsubstituted alkyl groups having 1 to 5 carbon atoms. 2 ,R 3 The unsubstituted alkyl group which may constitute the above formula is preferably a methyl group or an ethyl group.

[0080] Furthermore, R in formula (IV) and (d) 2 ,R 3 The fluorine-substituted alkyl group that can constitute the above formula is not particularly limited, and examples thereof include groups having a structure in which some or all of the hydrogen atoms in an alkyl group are substituted with fluorine atoms.

[0081] From the viewpoint of improving the ease of preparation of the copolymer B, it is preferable that the number of R 2 and / or R 3 are all preferably hydrogen atoms or unsubstituted alkyl groups, more preferably hydrogen atoms or unsubstituted alkyl groups having 1 to 5 carbon atoms, and most preferably hydrogen atoms.

[0082] The monomer (d) represented by the above formula (d) capable of forming the monomer unit (IV) represented by the above formula (IV) is not particularly limited, and examples thereof include α-methylstyrene (AMS) and its derivatives (e.g., 4-fluoro-α-methylstyrene: 4FAMS) such as the following monomers (d-1) to (d-11). [ka]

[0083] From the viewpoints of ease of preparation of copolymer B and improvement of severability of the main chain when irradiated with an electron beam or the like, the monomer (d) represented by the above formula (d) capable of forming the monomer unit (IV) is preferably α-methylstyrene or 4-fluoro-α-methylstyrene. That is, copolymer B preferably has an α-methylstyrene unit or a 4-fluoro-α-methylstyrene unit.

[0084] The proportion of the monomer units (IV) in all the monomer units constituting the copolymer B is not particularly limited, and can be, for example, 30 mol % or more and 70 mol % or less.

[0085] -Properties of copolymer B- =Weight average molecular weight (Mw)= The weight average molecular weight (Mw) of copolymer B is preferably 10000 or more, more preferably 17000 or more, even more preferably 25000 or more, and preferably 250000 or less, more preferably 180000 or less, and even more preferably 50000 or less. If the weight average molecular weight (Mw) of copolymer B is the above lower limit or more, it is possible to suppress excessive increase in the solubility of the resist film in the developer at a low irradiation dose. In addition, if the weight average molecular weight (Mw) of copolymer B is the above upper limit or less, it is easy to prepare a positive resist composition.

[0086] =Number average molecular weight (Mn)= The number average molecular weight (Mn) of copolymer B is preferably 7000 or more, more preferably 10000 or more, and preferably 150000 or less. If the number average molecular weight of copolymer B is equal to or more than the above lower limit, excessive increase in the solubility of the resist film in the developer at a low dose of irradiation can be further suppressed, and a resist pattern with further improved contrast can be formed. In addition, if the number average molecular weight of copolymer B is equal to or less than the above upper limit, preparation of a positive resist composition is further facilitated.

[0087] =Molecular weight distribution (Mw / Mn)= The molecular weight distribution (Mw / Mn) of copolymer B is preferably 1.10 or more, more preferably 1.20 or more, and preferably 1.70 or less, and more preferably 1.65 or less. When the molecular weight distribution (Mw / Mn) of copolymer B is equal to or more than the lower limit, the ease of production of copolymer B can be improved. When the molecular weight distribution (Mw / Mn) of copolymer B is equal to or less than the upper limit, the contrast of the obtained resist pattern can be further improved.

[0088] -Method for preparing copolymer B- The copolymer B having the above-mentioned monomer unit (III) and monomer unit (IV) is not particularly limited, and can be prepared, for example, by polymerizing a monomer composition containing monomer (c) and monomer (d), recovering the obtained copolymer, and optionally purifying it. Here, the polymerization method and purification method are not particularly limited, and can be the same as the polymerization method and purification method of the above-mentioned copolymer A. In addition, when preparing the copolymer B, it is preferable to use a polymerization initiator, and for example, a polymerization initiator such as azobisisobutyronitrile can be suitably used.

[0089] 〔solvent〕 There are no particular limitations on the solvent contained in the positive resist composition, so long as it is a solvent that is capable of dissolving the above-mentioned Copolymer A and Copolymer B, and it is possible to use known solvents such as those described in Japanese Patent No. 5938536. Among these, from the standpoint of obtaining a positive resist composition with an appropriate viscosity and improving the coatability of the positive resist composition, it is preferable to use anisole, propylene glycol monomethyl ether acetate (PGMEA), cyclopentanone, cyclohexanone, or isoamyl acetate as the solvent.

[0090] <Preparation of Positive Resist Composition> The positive resist composition can be prepared by mixing the above-mentioned copolymer A, copolymer B, a solvent, and any known additives that can be used. In this case, the mixing method is not particularly limited, and the mixing may be performed by a known method. Alternatively, the positive resist composition may be prepared by mixing the components and then filtering the mixture.

[0091] [Filtration] Here, the method of filtering the mixture is not particularly limited, and for example, the mixture can be filtered using a filter. The filter is not particularly limited, and examples thereof include fluorocarbon, cellulose, nylon, polyester, and hydrocarbon filtration membranes. Among them, from the viewpoint of effectively preventing impurities such as metals from metal piping, etc., which may be used when preparing the copolymer A and the copolymer B, from being mixed into the positive resist composition, the material constituting the filter is preferably nylon, polyethylene, polypropylene, polytetrafluoroethylene, polyfluorocarbon such as Teflon (registered trademark), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), nylon, and a composite membrane of polyethylene and nylon. As the filter, for example, one disclosed in U.S. Pat. No. 6,103,122 may be used. In addition, the filter is commercially available as Zeta Plus (registered trademark) 40Q manufactured by CUNO Incorporated. Furthermore, the filter may contain a strong cationic or weak cationic ion exchange resin. Here, the average particle size of the ion exchange resin is not particularly limited, but is preferably 2 μm or more and 10 μm or less. Examples of cation exchange resins include sulfonated phenol-formaldehyde condensates, sulfonated phenol-benzaldehyde condensates, sulfonated styrene-divinylbenzene copolymers, sulfonated methacrylic acid-divinylbenzene copolymers, and other types of sulfonic or carboxylic acid group-containing polymers. + Counterion, NH 4 + Counterion or alkali metal counterion, e.g. K + and Na +Counterions are provided. The cation exchange resin preferably has hydrogen counterions. Examples of such cation exchange resins include H + Sulfonated styrene-divinylbenzene copolymers with counterions include Microlite® PrCH from Purolite Corp. Such cation exchange resins are commercially available as AMBERLYST® from Rohm and Haas.

[0092] Furthermore, the pore size of the filter is preferably from 0.001 μm to 1 μm. If the pore size of the filter is within the above range, it is possible to sufficiently prevent impurities such as metals from being mixed into the positive resist composition.

[0093] [Ratio of copolymer A and copolymer B] The ratio of copolymer A and copolymer B in the positive resist composition is not particularly limited, but the ratio of copolymer B is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on 100% by mass of the total of copolymer A and copolymer B. If the ratio of copolymer B is equal to or greater than the lower limit, the solubility of the resist film in the developer can be prevented from increasing excessively at a low dose of irradiation, and a resist pattern with improved contrast can be formed. If the ratio of copolymer B is equal to or less than the upper limit, the deterioration of the sensitivity of the positive resist can be prevented.

[0094] In the resist film forming step, the coating method and drying method of the positive resist composition are not particularly limited, and methods generally used for forming resist films can be used. Among them, heating (prebaking) is preferable as the drying method. In addition, the prebaking temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 140°C or higher from the viewpoint of improving the film density of the resist film, and is preferably 250°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower from the viewpoint of reducing the change in the molecular weight and molecular weight distribution of copolymer A and copolymer B in the resist film before and after prebaking. Furthermore, the prebaking time is preferably 10 seconds or more, more preferably 20 seconds or more, and even more preferably 30 seconds or more from the viewpoint of improving the film density of the resist film formed through prebaking, and is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less from the viewpoint of reducing the change in the molecular weight and molecular weight distribution of copolymer A and copolymer B in the resist film before and after prebaking.

[0095] <Exposure process> In the exposure process, the resist film formed in the resist film formation process is irradiated with ionizing radiation such as electron beams or EUV to draw a desired pattern. For the irradiation of electron beams, a known drawing device such as an electron beam drawing device or an EUV exposure device can be used.

[0096] <Post-exposure bake process> In the optional post-exposure bake step, the resist film exposed in the exposure step is heated, and the post-exposure bake step can reduce the surface roughness of the resist pattern.

[0097] Here, the heating temperature is preferably at least 70° C., more preferably at least 80° C., and even more preferably at least 90° C., and is preferably at most 200° C., more preferably at most 170° C., and even more preferably at most 150° C. If the heating temperature is within the above range, the clarity of the resist pattern can be improved while the surface roughness of the resist pattern can be effectively reduced.

[0098] In addition, the time for heating the resist film in the post-exposure bake step (heating time) is preferably 10 seconds or more, more preferably 20 seconds or more, and even more preferably 30 seconds or more. If the heating time is 10 seconds or more, the surface roughness of the resist pattern can be sufficiently reduced while improving the clarity of the resist pattern. On the other hand, from the viewpoint of production efficiency, the heating time is, for example, preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less.

[0099] The method for heating the resist film in the post-exposure bake step is not particularly limited, and examples thereof include a method for heating the resist film on a hot plate, a method for heating the resist film in an oven, and a method for blowing hot air onto the resist film.

[0100] <Developing process> In the development process, the exposed resist film (or the exposed and heated resist film if a post-exposure bake process is performed) is developed using a solubility parameter (SP value) of 8 (cal / cm 3 ) 1 / 2 The developing is carried out using a developer containing at least the following solvent:

[0101] [Developer] Here, the SP value of the developer is 7.9 (cal / cm 3 ) 1 / 2 It is preferable that the calorie content is 7.8 (cal / cm 3 ) 1 / 2 More preferably, it is 6.0 (cal / cm 3 ) 1 / 2It is preferable that the calorie content is 6.2 (cal / cm 3 ) 1 / 2 More preferably, it is 6.4 (cal / cm 3 ) 1 / 2 If the SP value of the developer is within the above range, the contrast of the resist pattern can be further increased.

[0102] And the SP value is 8 (cal / cm 3 ) 1 / 2 A developer containing at least a solvent with an SP value of 8 (cal / cm 3 ) 1 / 2 Solvents with an SP value of 8 (cal / cm2) or less can be used alone. 3 ) 1 / 2 A developer containing at least a solvent with an SP value of 8 (cal / cm 3 ) 1 / 2 Solvents with SP values ​​of 8 (cal / cm 3 ) 1 / 2 A mixed solvent containing a solvent different from the solvent described below (hereinafter referred to as "another solvent") can be used.

[0103] The developer has an SP value of 8 (cal / cm 3 ) 1 / 2 When a solvent with an SP value of 8 (cal / cm2) or less is used alone, the development process 3 ) 1 / 2 It is preferable that the development step includes a process (1) in which development is performed using a developer (1) having a solvent not exceeding 8 (cal / cm 2 ) and a process (2) in which development is performed using a developer (2) different from the developer (1), and that the processes (1) and (2) are performed in this order. 3 ) 1 / 2 By carrying out a development process (1) using the following solvent as a developer (1) and then carrying out a development process (2) using a developer (2) different from the developer (1), it is possible to efficiently form a resist pattern with less loss of the top of the resist pattern and with higher contrast.

[0104] The developer (1) has an SP value of 8 (cal / cm 3 ) 1 / 2 There is no particular limitation as long as the solvent has an SP value of 8 (cal / cm 3 ) 1 / 2 Here, the hydrocarbon solvent is preferably a hydrocarbon solvent having a carbon number of 12 or less, for example, a linear or branched aliphatic hydrocarbon having a carbon number of 7 to 10. If the carbon number is 7 or more, when the resist film is brought into contact with the developer (1) for development, the developer (1) can be uniformly applied to the surface of the resist film by suppressing volatilization of the developer (1). If the carbon number is 10 or less, the developer (1) can be easily removed in the rinsing step. Preferred hydrocarbon solvents include branched alkanes such as heptane, octane, nonane, and decane. The hydrocarbon solvent may be used alone or in combination of two or more.

[0105] The boiling point of the developer (1) is not particularly limited, but is preferably 80° C. or higher, more preferably 90° C. or higher, and is preferably 230° C. or lower, and is preferably 200° C. or lower. If the boiling point of the developer (1) is within the above lower limit, the volatilization of the developer (1) can be further suppressed when the resist film is brought into contact with the developer (1) for development, and the developer (1) can be more uniformly applied to the surface of the resist film. If the boiling point of the developer (1) is within the above upper limit, the developer (1) can be more easily removed in the rinsing step.

[0106] The developer (2) is not particularly limited as long as it is different from the developer (1). The SP value of the developer (2) is 8 (cal / cm 3 ) 1 / 2 More preferably, it is greater than 9 (cal / cm 3 ) 1 / 2 More preferably, it is 10 (cal / cm 3 ) 1 / 2More preferably, it is more than or equal to 10. As a preferred developer (2), for example, an alcohol solvent having 1 to 10 carbon atoms, preferably 5 or less carbon atoms, can be mentioned, specifically, for example, alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, and 3-pentanol. Among these, from the viewpoint of further increasing the contrast of the resist pattern, ethanol, 1-propanol, 2-propanol, and 1-butanol are preferred. These alcohols may be used alone or in combination of two or more.

[0107] As mentioned above, the SP value is 8 (cal / cm 3 ) 1 / 2 When using a mixed solvent containing a solvent with an SP value of 8 (cal / cm 3 ) 1 / 2 The mass ratio of the solvent with an SP value of 8 (cal / cm 3 ) 1 / 2 The ratio of the solvent (which is the same or less than 10:90:other solvent) is preferably 10:90 to 90:10, and more preferably 30:70 to 70:30. 3 ) 1 / 2 When the mass ratio of the mixed solvent containing the solvent specified below and another solvent is within the above range, the contrast of the resist pattern can be further improved.

[0108] Here, the SP value is 8 (cal / cm 3 ) 1 / 2 When using a mixed solvent containing a solvent with an SP value of 8 (cal / cm 3 ) 1 / 2 The solvent is not particularly limited, and for example, the above-mentioned hydrocarbon solvents can be preferably used. The other solvent is not particularly limited, and for example, the above-mentioned alcohol solvents can be preferably used.

[0109] The resist film can be developed, for example, by contacting the resist film with the above-mentioned developer. The method for contacting the resist film with the developer is not particularly limited, and known methods such as immersing the resist film in the developer or applying the developer to the resist film can be used.

[0110] The temperature of the developer during development is not particularly limited, but may be, for example, from 5° C. to 40° C. The development time may be, for example, from 10 seconds to 4 minutes.

[0111] The developer may be filtered before use, for example by the filtration method using a filter as explained above in the section "Preparation of a positive resist composition".

[0112] <Rinse process> In the optional rinsing step, the developer is removed after the development step, which can be done, for example, by using a rinsing liquid. Specific examples of the rinse liquid include the hydrocarbon solvents, alcohol solvents, and water exemplified in the section "Development step". Here, the rinse liquid may contain a surfactant. In addition, when selecting a rinse liquid, it is preferable to select a rinse liquid that is less likely to dissolve the resist film before the exposure step than the developer used in the development step and that is easily mixed with the developer.

[0113] The temperature of the rinse liquid during rinsing is not particularly limited, but may be, for example, from 5° C. to 40° C. The rinsing time may be, for example, from 5 seconds to 3 minutes.

[0114] Furthermore, the rinse solution used in the rinsing step may be filtered before use. Examples of the filtration method include the filtration method using a filter described above in the section "Preparation of a positive resist composition".

[0115] <Etching process> In the optional etching step, the underlayer film and / or the substrate are etched using the resist pattern as a mask to form a pattern in the underlayer film and / or the substrate. In this case, the number of etching steps is not particularly limited, and may be one or more. The etching may be dry etching or wet etching, but dry etching is preferred. Dry etching can be performed using a known dry etching device. The etching gas used in dry etching can be appropriately selected depending on the elemental composition of the underlying film or substrate to be etched. For example, CHF 3 , C.F. 4 , C 2 F 6 , C 3 F 8 ,SCIENCE FICTION 6 Fluorine gases such as Cl 2 , BCl 3 Chlorine gases such as O 2 , O 3 , H 2 Oxygen-based gases such as O; H 2 , N.H. 3 , CO, CO 2 , C.H. 4 , C 2 H 2 , C 2 H 4 , C 2 H 6 , C 3 H 4 , C 3 H 6 , C 3 H 8 , HF, HI, HBr, HCl, NO, NH 3 , BCl 3 Reducing gases such as He, N 2 , and inert gases such as Ar. These gases may be used alone or in combination of two or more. For dry etching of an inorganic underlayer film, an oxygen-based gas is usually used. For dry etching of a substrate, a fluorine-based gas is usually used, and a mixture of a fluorine-based gas and an inert gas is preferably used.

[0116] Furthermore, if necessary, the underlayer film remaining on the substrate may be removed before or after etching the substrate. When the underlayer film is removed before etching the substrate, the underlayer film may be a patterned underlayer film or an unpatterned underlayer film.

[0117] Here, the method of removing the underlayer film includes, for example, the above-mentioned dry etching. In addition, in the case of an inorganic underlayer film, a liquid such as a basic liquid or an acid liquid, preferably a basic liquid, may be brought into contact with the underlayer film to remove the underlayer film. Here, the basic liquid is not particularly limited, and examples thereof include alkaline hydrogen peroxide and the like. The method of removing the underlayer film by wet stripping using alkaline hydrogen peroxide is not particularly limited as long as the underlayer film and alkaline hydrogen peroxide can be brought into contact with each other for a certain period of time under heating conditions, and examples thereof include a method of immersing the underlayer film in heated alkaline hydrogen peroxide, a method of spraying alkaline hydrogen peroxide on the underlayer film in a heated environment, and a method of coating the underlayer film with heated alkaline hydrogen peroxide. After performing any of these methods, the substrate is washed with water and dried to obtain a substrate from which the underlayer film has been removed.

[0118] (Etching resistance of resist film) The resist film obtained by the method for forming a resist pattern of the present invention has excellent etching resistance, and is particularly excellent in dry etching resistance. Note that the higher the ratio of the carbon amount per unit volume of copolymer A and copolymer B contained in the positive resist composition, the more excellent the dry etching resistance of the resist film tends to be.

[0119] According to the method of forming a resist pattern of the present invention, for example, a laminate comprising a resist film having a two-layer structure as described below can be obtained.

[0120] (Laminate) The laminate obtained by the method for forming a resist pattern of the present invention comprises a substrate and a resist film formed on the substrate, and the resist film comprises a lower layer provided on the substrate and an upper layer provided on the lower layer. The lower layer is composed of the above-mentioned copolymer A, and the upper layer is composed of the above-mentioned copolymer B. The resist film of the laminate of the present invention can be formed by the method for forming a resist pattern of the present invention. EXAMPLES

[0121] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the examples and comparative examples, the number average molecular weight, weight average molecular weight and molecular weight distribution of the copolymer, the surface free energy and the solubility parameter of the developer were measured by the following methods.

[0122] <Number average molecular weight, weight average molecular weight and molecular weight distribution> The number average molecular weight (Mn) and weight average molecular weight (Mw) of the obtained copolymer A and copolymer B were measured by gel permeation chromatography, and the molecular weight distribution (Mw / Mn) was calculated. Specifically, the number average molecular weight (Mn) and weight average molecular weight (Mw) of copolymer A and copolymer B were determined in terms of standard polystyrene using a gel permeation chromatograph (Tosoh Corporation, HLC-8220) and tetrahydrofuran as a developing solvent. The molecular weight distribution (Mw / Mn) was then calculated. It was confirmed that each of the obtained copolymers A and B did not substantially contain components with a weight average molecular weight (Mw) of less than 1000.

[0123] <Surface free energy> <<Surface free energy of copolymer A>> The copolymer A1 prepared in Preparation Example 1 as the copolymer A was dissolved in isoamyl acetate to prepare a composition (A) for measuring surface free energy at a concentration of 3% by mass. A film (membrane) was produced using the obtained composition (A) by the following method. <<How to make the film>> Using a spin coater (MS-A150, manufactured by Mikasa), the composition (A) prepared as described above was applied to a silicon wafer having a diameter of 4 inches to a thickness of 50 nm. The applied composition (A) was then heated on a hot plate at a temperature of 170° C. for 1 minute to form a resist film on the silicon wafer. Next, the contact angle of the obtained film (membrane) with two solvents (water and diiodomethane) whose surface tension, polarity term (p) and dispersion force term (d) are known was measured under the following conditions using a contact angle meter (Drop Master 700, manufactured by Kyowa Interface Science Co., Ltd.), and the surface free energy was evaluated by the Owens-Wendt (extended Fowkes equation) method, and the surface free energy of the film (membrane) was calculated. The surface free energy of the obtained film (membrane) was taken as the surface free energy of copolymer A. <<Conditions for contact angle measurement>> Needle: Metal needle 22G (water), Teflon (registered trademark) coated 22G (diiodomethane) Wait time: 1000ms Volume: 1.8μL Liquid recognition: Water 50dat, diiodomethane 100dat Temperature: 23℃ <<Surface free energy of copolymer B>> The surface free energy of copolymer B was determined in the same manner as in the calculation of the surface free energy of copolymer A described above, except that copolymer B prepared in Preparation Examples 2 to 7 was used instead of copolymer A.

[0124] <Solubility parameter of developer (SP value)> The solubility parameters (SP values) of the developers used in the examples and comparative examples were literature values ​​calculated by the Hansen method.

[0125] <Preparation of Copolymer A> <<Preparation Example 1: Preparation of Copolymer A1>> [Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap with a solid content of 18%] 100g of ion-exchanged water was prepared, heated to 70°C while stirring, and 8.40g of potassium hydroxide (49% aqueous solution) was added. Next, 19.6g of beef tallow 45° hardened fatty acid HFA (NOF Corp.) was added at a rate of 1.28g / min, and then 0.126g of potassium silicate was added. The mixture was then stirred at 80°C for more than 2 hours to obtain an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18%. [Synthesis of polymers] In a glass ampoule containing a stirrer, 3 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl (ACAFPh) as monomer (a) and 1.066 g of α-methylstyrene as monomer (b) were added. In addition, 6.771 g of ion-exchanged water was added to 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap prepared above with a solid content of 18% to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was then heated to 75°C and polymerization reaction was carried out for 1 hour. Next, 10 g of tetrahydrofuran (THF) was added to the system, and the resulting solution was dropped into 100 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The resulting polymer was a copolymer containing 54 mol% of α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and 46 mol% of α-methylstyrene units. Thereafter, the number average molecular weight, weight average molecular weight and molecular weight distribution of the obtained copolymer (copolymer A1 before purification) were measured. The results are shown in Table 1. [Purification of polymer] The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) 33:67) to precipitate a white coagulated product (a copolymer containing α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and α-methylstyrene units). The solution containing the precipitated copolymer was then filtered using a Kiriyama funnel to obtain a white copolymer (a copolymer containing 54 mol% of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and 46 mol% of α-methylstyrene units). Thereafter, the number average molecular weight, weight average molecular weight, molecular weight distribution, and surface free energy of the obtained copolymer (copolymer A1 after purification) were measured. The results are shown in Table 1.

[0126] <Preparation Example 2: Preparation of Copolymer B1> [Synthesis of polymers] A monomer composition containing 3 g of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate (ACAPFP) as monomer (c), 3.476 g of α-methylstyrene as monomer (d), 0.0551 g of azobisisobutyronitrile as a polymerization initiator, and 1.6205 g of cyclopentanone as a solvent was placed in a glass container, the glass container was sealed and replaced with nitrogen, and the mixture was stirred in a constant temperature bath at 78° C. under a nitrogen atmosphere for 6 hours. After that, the temperature was returned to room temperature, the glass container was opened to the atmosphere, and 10 g of THF was added to the obtained solution. The solution to which THF had been added was then dropped into 100 g of MeOH as a solvent to precipitate a polymer. The solution containing the precipitated polymer was then filtered using a Kiriyama funnel to obtain a white coagulated product (polymer). The obtained polymer was a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units. Thereafter, the obtained copolymer (copolymer B1 before purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1. [Purification of polymer] Next, the obtained polymer was dissolved in 100g of THF, and the obtained solution was dropped into 100g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) 6:94) to precipitate a white coagulated product (a copolymer containing 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and α-methylstyrene units). Then, the solution containing the precipitated coagulated product was filtered using a Kiriyama funnel to obtain a white polymer (a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units). Thereafter, the obtained copolymer (copolymer B1 after purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0127] <<Preparation Example 3: Preparation of Copolymer B2>> [Synthesis of polymers] The same procedure as in Preparation Example 2 was carried out, except that the amount of azobisisobutyronitrile used as the polymerization initiator was changed to 0.02755 g and the obtained polymer was not purified. A copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units was obtained as a white coagulated product (polymer). The obtained copolymer was designated as Copolymer B2, and various measurements were carried out on Copolymer B2 in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0128] <<Preparation Example 4: Preparation of Copolymer B3>> [Synthesis of polymers] Except for changing the amount of azobisisobutyronitrile as a polymerization initiator to 0.00551 g, the same operation as in Preparation Example 2 was carried out to obtain a white coagulated material (polymerization product). The obtained polymerization product was a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units. Thereafter, the obtained copolymer (copolymer B3 before purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1. [Purification of polymer] Next, the obtained polymer was dissolved in 100g of THF, and the obtained solution was dropped into 100g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) 15:85) to precipitate a white coagulated product (a copolymer containing 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and α-methylstyrene units). Then, the solution containing the precipitated coagulated product was filtered using a Kiriyama funnel to obtain a white polymer (a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units). Thereafter, the obtained copolymer (copolymer B3 after purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0129] <<Preparation Example 5: Preparation of Copolymer B4>> [Synthesis of polymers] Except for changing the amount of azobisisobutyronitrile as a polymerization initiator to 0.02755 g, the same operation as in Preparation Example 2 was carried out to obtain a white coagulated material (polymerization product). The obtained polymerization product was a copolymer containing 50 mol% of 2,2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units. Thereafter, the obtained copolymer (copolymer B4 before purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1. [Purification of polymer] Next, the obtained polymer was dissolved in 100g of THF, and the obtained solution was dropped into 100g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) 9:91) to precipitate a white coagulated product (a copolymer containing 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and α-methylstyrene units). After that, the solution containing the precipitated coagulated product was filtered with a Kiriyama funnel to obtain a white polymer (a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units). Thereafter, the obtained copolymer (copolymer B4 after purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0130] <<Preparation Example 6: Preparation of Copolymer B5>> [Synthesis of polymers] A white coagulated material (polymer) was obtained by the same procedure as in Preparation Example 2, except that the amount of azobisisobutyronitrile used as a polymerization initiator was changed to 0.1102 g. The obtained polymer was a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units. Thereafter, the obtained copolymer (copolymer B5 before purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1. [Purification of polymer] Next, the obtained polymer was dissolved in 100g of THF, and the obtained solution was dropped into 100g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) 5:95) to precipitate a white coagulated product (a copolymer containing 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and α-methylstyrene units). Then, the solution containing the precipitated coagulated product was filtered using a Kiriyama funnel to obtain a white polymer (a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate units and 50 mol% of α-methylstyrene units). Thereafter, the obtained copolymer (copolymer B5 after purification) was subjected to various measurements in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0131] <<Preparation Example 7: Preparation of Copolymer B6>> [Synthesis of polymers] Except for changing the amount of azobisisobutyronitrile used as a polymerization initiator to 0.551 g and not purifying the obtained polymer, the same procedure as in Preparation Example 2 was carried out to obtain a white polymer (a copolymer containing 50 mol% of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate and 50 mol% of α-methylstyrene). The obtained copolymer was designated as Copolymer B6, and various measurements were carried out on Copolymer B6 in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0132] [Table 1]

[0133] In Table 1, "ACAFPh" stands for α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl; "ACAPFP" stands for 2,2,3,3,3-pentafluoropropyl α-chloroacrylate. "KORR (18%) soap" refers to an aqueous solution of half-hardened tallow fatty acid potassium soap with a solid content of 18%. "THF" stands for tetrahydrofuran; "MeOH" stands for methanol.

[0134] Example 1 <Preparation of Positive Resist Composition> Copolymer A1 prepared in Preparation Example 1 was used as copolymer A, and copolymer B1 prepared in Preparation Example 2 was used as copolymer B. Copolymer A and copolymer B were dissolved in isoamyl acetate as a solvent so that the mass ratio (copolymer A:copolymer B) was 90:10. A positive resist composition containing copolymer A and copolymer B at a concentration of 3 mass% was prepared.

[0135] <Formation of Resist Pattern> <<Resist film formation process>> Using a spin coater (MS-A150, manufactured by Mikasa), the positive resist composition obtained as described above was applied to a silicon wafer having a diameter of 4 inches to a thickness of 50 nm. The applied positive resist composition was then heated on a hot plate at a temperature of 170° C. for 1 minute to form a resist film on the silicon wafer. <<Exposure process>> The formed resist film was exposed to light. Specifically, an electron beam lithography system (ELS-S50, manufactured by Elionix) was used to draw multiple patterns (dimensions 500 μm × 500 μm) on the resist film with different electron beam doses. The electron beam dose was 4 μC / cm 2 to 200μC / cm 2 Within the range of 4μC / cm 2 Each was made different. <<Post-exposure bake process>> The exposed resist film was heated on a hot plate at 100° C. for 1 minute. <<Developing process>> The exposed resist film was developed using a developer. Specifically, heptane (SP value: 7.4 (cal / cm)) was used as the developer (1). 3 ) 1 / 2 Development processing was carried out at a temperature of 23°C for 1 minute using ethanol (SP value: 12.7 (cal / cm3) as developer (2) (processing (1)). After that, the developer (1) was removed by nitrogen blowing. 3 ) 1 / 2 The developer was then subjected to development processing at 23° C. for 1 minute using a developing solution (boiling point: 78° C.) (processing (2)). Thereafter, the developer (2) was removed by nitrogen blowing.

[0136] <γ value> The thickness of the resist film in the portion where the pattern was written as described above was measured with an optical film thickness meter (Lambda Ace, manufactured by SCREEN Semiconductor Solutions), and a sensitivity curve was created showing the relationship between the common logarithm of the total dose of the electron beam and the remaining film ratio of the resist film after development (= film thickness of the resist film after development / film thickness of the resist film formed on the silicon wafer). Then, for the obtained sensitivity curve (horizontal axis: common logarithm of the total dose of electron beam irradiation, vertical axis: resist film residual ratio (0≦remaining ratio≦1.00)), the sensitivity curve was fitted to a quadratic function in the range of residual ratios of 0.20 to 0.80, and a straight line (an approximation line of the slope of the sensitivity curve) was created connecting the point where the residual ratio was 0 and the point where the residual ratio was 0.50 on the obtained quadratic function (a function of the residual ratio and the common logarithm of the total dose). The γ value was calculated using the following formula. The results are shown in Table 2. In the following formula, E 0 is the logarithm of the total irradiation dose obtained by fitting the sensitivity curve to a quadratic function in the range of the remaining film ratio of 0.20 to 0.80, and substituting the remaining film ratio of 0 for the obtained quadratic function (a function of the remaining film ratio and the common logarithm of the total irradiation dose). 1 is the logarithm of the total irradiation dose obtained when a straight line (an approximation line of the slope of the sensitivity curve) is created connecting the point of the residual film ratio 0 and the point of the residual film ratio 0.50 on the obtained quadratic function, and a residual film ratio of 1.00 is substituted for the obtained straight line (a function of the residual film ratio and the common logarithm of the total irradiation dose).The following formula represents the slope of the straight line between the residual film ratios 0 and 1.00.Note that if the γ value is greater than 9.8, the slope of the sensitivity curve is large, indicating that a resist pattern with high contrast can be formed well.

number

[0137] <eth> The initial thickness T of the resist film obtained above 0 was measured using an optical film thickness gauge (Lambda Ace, manufactured by SCREEN Semiconductor Solutions). The total electron beam irradiation dose Eth (μC / cm2) was calculated when the residual film rate of the straight line (approximation line of the slope of the sensitivity curve) obtained when calculating the γ value became 0. 2 The results are shown in Table 2. The smaller the Eth value, the higher the sensitivity of the resist film and the higher the efficiency of forming the resist pattern.

[0138] (Examples 2 to 3) <Preparation of Positive Resist Composition> When preparing the positive resist compositions, copolymer B2 was used as copolymer B. The positive resist compositions were prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 80:20 (Example 2) and 70:30 (Example 3). <Formation of Resist Pattern> Except for using the positive resist composition prepared as above, a resist pattern was formed and various measurements were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0139] (Examples 4 to 11) <Preparation of Positive Resist Composition> When preparing the positive resist compositions, copolymer B1 (Example 6), copolymer B3 (Examples 4 and 10), copolymer B4 (Examples 5, 7 and 11), and copolymer B5 (Examples 8 and 9) were used as copolymer B. The positive resist compositions were prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 80:20 (Examples 4, 6, 8 and 11), 70:30 (Examples 5 and 9), and 90:10 (Examples 7 and 10). <Formation of Resist Pattern> In the development step, isopropyl alcohol (SP value: 11.5 (cal / cm 3 ) 1 / 2 , boiling point: 83°C, Examples 4 to 6), 1-propanol (SP value: 11.9 (cal / cm 3 ) 1 / 2 , boiling point: 97°C, Examples 7 to 9), 1-butanol (SP value: 11.4 (cal / cm 3 ) 1 / 2 Treatment (2) was carried out using the same solvent as in Example 1 (boiling point: 117° C., Examples 10 and 11). Except for this, a resist pattern was formed in the same manner as in Example 1, and various measurements were carried out. The results are shown in Table 2.

[0140] [Table 2]

[0141] (Examples 12 to 18) <Preparation of Positive Resist Composition> Copolymer B1 (Examples 12, 16, and 18) and copolymer B4 (Examples 13 to 15 and 17) were used as copolymer B. Positive resist compositions were prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 90:10 (Examples 12 and 15), 80:20 (Examples 13, 16, and 17), and 70:30 (Examples 14 and 18). <Formation of Resist Pattern> In the development process, octane (SP value: 7.5 cal / cm) was used as the developer (1). 3 ) 1 / 2 Treatment (1) was carried out using ethanol (Example 12), isopropyl alcohol (Examples 13 and 14), 1-propanol (Examples 15 and 16), and 1-butanol (Examples 17 and 18) as the developer (2). Otherwise, resist patterns were formed in the same manner as in Example 1, and various measurements were carried out. The results are shown in Table 3.

[0142] (Examples 19 to 22) <Preparation of Positive Resist Composition> Copolymer B1 (Examples 21 and 22) and copolymer B4 (Examples 19 and 20) were used as copolymer B. Positive resist compositions were prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to the copolymer (copolymer A:copolymer B) was 90:10 (Example 19), 80:20 (Examples 20 and 21), and 70:30 (Example 22). <Formation of Resist Pattern> In the development process, nonane (SP value: 7.7 cal) was used as developer (1). 3 / cm) 1 / 2 Treatment (1) was carried out using a developer (2) selected from the above-mentioned isopropyl alcohol (Examples 19 and 20), the above-mentioned 1-propanol (Example 21), and the above-mentioned 1-butanol (Example 22). Except for this, resist patterns were formed in the same manner as in Example 1, and various measurements were carried out. The results are shown in Table 3.

[0143] [Table 3]

[0144] (Examples 23 to 31) <Preparation of Positive Resist Composition> Copolymer B1 (Examples 26 and 30), copolymer B2 (Example 29), copolymer B3 (Example 24), copolymer B4 (Examples 25 and 28), copolymer B5 (Examples 27 and 31), and copolymer B6 (Example 23) were used as copolymer B. Positive resist compositions were prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 80:20 (Examples 23, 25, 30, and 31), 90:10 (Examples 24 and 28), and 70:30 (Examples 26, 27, and 29). <Formation of Resist Pattern> In the development process, decane (SP value: 7.7) cal / cm was used as the developer (1). 3 ) 1 / 2 Treatment (1) was carried out using ethanol (Example 23), isopropyl alcohol (Examples 24 to 27), 1-propanol (Examples 28 and 29), and 1-butanol (Examples 30 and 31) as the developer (2). Otherwise, a resist pattern was formed in the same manner as in Example 1, and various measurements were carried out. The results are shown in Table 4.

[0145] [Table 4]

[0146] Example 32 <Preparation of Positive Resist Composition> Copolymer B3 was used as copolymer B. A positive resist composition was prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 80:20. <Formation of Resist Pattern> In the developing step, the exposed resist film was developed using a mixed solvent containing the above-mentioned heptane and the above-mentioned isopropyl alcohol in a mass ratio (heptane:isopropyl alcohol) of 50:50 as a developer. Otherwise, a resist pattern was formed in the same manner as in Example 1, and various measurements were performed. The results are shown in Table 5.

[0147] (Examples 33 to 35) <Preparation of Positive Resist Composition> Copolymer B4 was used as copolymer B. A positive resist composition was prepared in the same manner as in Example 1, except that the mass ratio of copolymer A to copolymer B (copolymer A:copolymer B) was 80:20. <Formation of Resist Pattern> In the development step, the exposed resist film was developed using a mixed solvent containing the above-mentioned octane and the above-mentioned isopropyl alcohol in a mass ratio (octane:isopropyl alcohol) of 50:50 (Example 33), a mixed solvent containing the above-mentioned nonane and the above-mentioned isopropyl alcohol in a mass ratio (nonane:isopropyl alcohol) of 50:50 (Example 34), and a mixed solvent containing the above-mentioned decane and the above-mentioned isopropyl alcohol in a mass ratio (decane:isopropyl alcohol) of 50:50 (Example 35). Otherwise, a resist pattern was formed in the same manner as in Example 32, and various measurements were performed. The results are shown in Table 5.

[0148] [Table 5]

[0149] Comparative Example 1 <Preparation of Positive Resist Composition> Copolymer B was not used, and only copolymer A1 was used as copolymer A. Copolymer A1 was then dissolved in isoamyl acetate as a solvent to prepare a positive resist composition with a concentration of 3 mass %. <Formation of Resist Pattern> In the development step, only the process (1) was carried out using the above-mentioned ethanol as the developer (1), and the process (2) using the developer (2) was not carried out. Otherwise, a resist pattern was formed in the same manner as in Example 1, and various measurements were carried out. The results are shown in Table 6.

[0150] (Comparative Examples 2 to 4) <Preparation of Positive Resist Composition> In the same manner as in Comparative Example 1, a positive resist composition was prepared. <Formation of Resist Pattern> In the developing step, resist patterns were formed and various measurements were carried out in the same manner as in Comparative Example 1, except that the above-mentioned isopropyl alcohol (Comparative Example 2), the above-mentioned 1-propanol (Comparative Example 3), or the above-mentioned 1-butanol (Comparative Example 4) was used as the developer (1). The results are shown in Table 6.

[0151] [Table 6]

[0152] From Tables 2 to 5, a resist film was formed using a positive resist composition containing the specified copolymer A and copolymer B, and after the resulting resist film was exposed, the SP value was 8 (cal / cm 3 ) 1 / 2 In Examples 1 to 35, which were developed using a developer containing at least the following solvent, the Eth and γ values ​​show that the sensitivity of the resist film was high and the efficiency of resist pattern formation was high, resulting in little loss of the resist pattern top. In addition, in Examples 1 to 35, the γ values ​​exceeded 9.8, showing that a resist pattern with high contrast could be formed. On the other hand, from Table 6, a resist film was formed using a positive resist composition containing only a specific copolymer A, and after the resist film was exposed, the SP value was 8 (cal / cm 3 ) 1 / 2 In Comparative Examples 1 to 4, in which development was performed using a developer exceeding 100 gamma values, the gamma values ​​were 9.8 or less. This shows that in Comparative Examples 1 to 4, the reduction in the top of the resist pattern was small and it was not possible to form a resist pattern with high contrast. [Industrial Applicability]

[0153] According to the method of forming a resist pattern of the present invention, it is possible to form a resist pattern with high contrast and with little loss of the top of the resist pattern.< / eth>

Claims

1. The present invention comprises a main chain cleavage type copolymer A containing a fluorine substituent, a main chain cleavage type copolymer B containing a fluorine substituent, and a solvent, and the difference between the surface free energy of the copolymer A and the surface free energy of the copolymer B is 4 mJ / m 2 a resist film forming step of forming a resist film using the positive resist composition described above; an exposure step of exposing the resist film to light; The exposed resist film was treated with a solvent having a solubility parameter of 8 (cal / cm 3 ) 1/2 and a developing step of developing using a developer containing at least the following solvent:

2. The copolymer A is represented by the following formula (I): 【Chemistry 1】 [In formula (I), L is a divalent linking group having a fluorine atom, and Ar is an aromatic ring group which may have a substituent.], The following formula (II): 【Chemistry 2】 [In formula (II), R 1 is an alkyl group, R 2 is a hydrogen atom, an alkyl group, a halogen atom, a halogenated alkyl group, a hydroxyl group, a carboxyl group, or a halogenated carboxyl group; R 3 represents a hydrogen atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, p and q each represent an integer of 0 to 5, and p+q=5. and a monomer unit (II) represented by the following formula (II):

3. The copolymer B is represented by the following formula (III): 【Chemistry 3】 [In formula (III), R 1 is an organic group having 5 to 7 fluorine atoms. A monomer unit (III) represented by The following formula (IV): 【Chemistry 4】 [In formula (IV), R 1 is an alkyl group, R 2 is a hydrogen atom, a fluorine atom, an unsubstituted alkyl group or an alkyl group substituted with a fluorine atom, R 3 represents a hydrogen atom, an unsubstituted alkyl group, or an alkyl group substituted with a fluorine atom, p and q each represent an integer of 0 to 5, and p+q=5. and a monomer (IV) represented by the following formula (1):

4. The developing step is carried out using a solution having a solubility parameter of 8 (cal / cm 3 ) 1/2 The method includes a process (1) of developing using a developer (1) that is one of the following solvents, and a process (2) of developing using a developer (2) that is different from the developer (1), The method for forming a resist pattern according to any one of claims 1 to 3, wherein the treatment (1) and the treatment (2) are carried out in this order.

5. 5. The method of forming a resist pattern according to claim 4, wherein the developer (1) is a hydrocarbon solvent.

6. 6. The method for forming a resist pattern according to claim 4, wherein the developer (2) is an alcohol-based solvent.

Citation Information

Patent Citations

  • Resist material and formation of resist micropattern using it

    JP1983113932A

  • Method for developing resist

    JP1986249049A

  • Method for developing resist, method for forming resist pattern, method for manufacturing mold, and developing solution used for the same

    JP2013210411A

  • Copolymer and positive resist composition

    JP2018154754A

  • Positive resist composition and resist pattern forming kit

    JP2021033293A